The European cancer burden in 2020: Incidence and mortality estimates for 40 countries and 25 major cancers. (November 2021) - Dyba, Tadeusz; Randi, Giorgia; Bray, Freddie; Martos, Carmen; Giusti, Francesco; Nicholson, Nicholas; Gavin, Anna; Flego, Manuela; Neamtiu, Luciana; Dimitrova, Nadya; Negrão Carvalho, Raquel; Ferlay, Jacques; et al.
Abstract: Introduction: Europe is an important focus for compiling accurate and up-to-date world cancer statistics owing to its large share of the world's total cancer burden. This article presents incidence and mortality estimates for 25 major cancers across 40 individual countries within European areas and the European Union (EU-27) for the year 2020. Methods: The estimated national incidence and mortality rates are based on statistical methodology previously applied and verified using the most recently collected incidence data from 151 population-based cancer registries, mortality data and 2020 population estimates. Results: Estimates reveal 4 million new cases of cancer (excluding non-melanoma skin cancer) and 1.9 million cancer-related deaths. The most common cancers are: breast in women (530, 000 cases), colorectum (520, 000), lung (480, 000) and prostate (470, 000). These four cancers account for half the overall cancer burden in Europe. The most common causes of cancer deaths are: lung (380, 000), colorectal (250, 000), breast (140, 000) and pancreatic (130, 000) cancers. In EU-27, the estimated new cancer cases are approximately 1.4 million in males and 1.2 million in females, with over 710, 000 estimated cancer deaths in males and 560, 000 in females. Conclusion: The 2020 estimates provide a basis for establishing priorities in cancer-control measures across Europe. The long-established role of cancer registries in cancer surveillance and the evaluation of cancer control measures remain fundamental in formulating and adapting national cancer plans and pan-European health policies. Given the estimates are built on recorded data prior to the onset of coronavirus disease 2019 (COVID-19), they do not take into account the impact of the pandemic. Highlights: The 2020 incidence estimates derived from 151 population-based cancer registries' data. Over 4 million new cancer cases and 1.9 million cancer-related deaths are estimated in Europe for 2020. Half the overall cancer diagnoses are from breast, colorectal, lung and prostate cancers. The most common cancer-related deaths are from lung, colorectal, breast and pancreatic cancers. The 2020 estimates are key to assess and monitor cancer-control measures across Europe.